Free-Weight Augmentation With Elastic Bands Improves Bench Press Kinematics in Professional Rugby Players. Issue 9 (September 2016) - García-López, David; Hernández-Sánchez, Sonsoles; Martín, Esperanza; Marín, Pedro J.; Zarzosa, Fernando; Herrero, Azael J.
Abstract : Abstract: García-López, D, Hernández-Sánchez, S, Martín, E, Marín, PJ, Zarzosa, F, and Herrero, AJ. Free-weight augmentation with elastic bands improves bench press kinematics in professional rugby players. J Strength Cond Res 30(9): 2493–2499, 2016—This study aimed to investigate the effects of combining elastic bands to free weight resistance (EB + FWR) on the acceleration-deceleration and velocity profiles of the bench press in professional rugby players and recreationally trained subjects. Sixteen male subjects (8 rugby players and 8 recreationally trained subjects) were randomly assigned to complete 2 experimental conditions in a crossover fashion: EB + FWR and FWR. In both conditions, subjects performed 1 bench press set to volitional exhaustion with a load equivalent to the 85% of 1 repetition maximum (1RM). In the EB + FWR condition, the contribution of elastic resistance was approximately 20% of the selected load (85% 1RM). Results indicate that EB + FWR condition increased significantly the range of concentric movement in which the barbell is accelerated. This increase was significantly higher in rugby players (35%) in comparison with recreationally trained subjects (13%). Maximal velocity was also increased in EB + FWR (17%), when compared with FWR condition. These results suggest that when combined with variable resistance (i.e., EB), the external resistance seems to be more evenly distributed over the full range of motion, decreasing the need for dramatic deceleration at the end of the concentric phase. The present data also indicate that the kinematic benefits of an EB + FWR approach seems to be more prominent in athletes from modalities in which high level of strength and power are required (i.e., rugby players).